Exenatide induces an increase in vasodilatory and a decrease in vasoconstrictive mediators. Issue 5 (22nd February 2017) - Chaudhuri, Ajay; Ghanim, Husam; Makdissi, Antoine; Green, Kelly; Abuaysheh, Sanaa; Batra, Manav; D. Kuhadiya, Nitesh; Dandona, Paresh
Abstract : In view of the known vasodilatory effects of glucagon‐like peptide‐1 and exenatide, we investigated the effects of exenatide on vasoactive factors. We analysed blood samples and mononuclear cells (MNCs) from a previous study, collected after a single dose and 12 weeks of exenatide or placebo treatment in a series of 24 patients with type 2 diabetes mellitus. After exenatide treatment, plasma concentrations of atrial natriuretic peptide, cyclic guanyl monophosphate (cGMP) and cyclic adenyl monophosphate increased significantly at 12 weeks. Plasma cGMP and adenylate cyclase expression in MNCs increased significantly after a single dose. Angiotensinogen concentration fell significantly 2 hours after a single dose and at 12 weeks, while renin and angiotensin II levels fell significantly only after a single dose and not after 12 weeks of treatment. Exenatide also suppressed the plasma concentration of transforming growth factor‐β and the expression of P311 in MNCs at 12 weeks. Thus, exenatide induces an increase in a series of vasodilators, while suppressing the renin‐angiotensin system. These changes may contribute to the overall vasodilatory effect of exenatide.